Miniaturized 3-bit phase shifter for 60 GHz phased-array in 65 nm CMOS technology - Meng, Fanyi (2013)
The paper presents a compact 3-bit 90° phase shifter for phased-array applications at the 60-GHz ISM band (IEEE 802.11ad standard). The designed phase shifter is based on reflective-type topology using the proposed reflective loads with binary-weighted digitally-controlled varactor arrays and the transformer-type directional coupler. The measured eight output states of the implemented phase shifter in 65-nm CMOS technology, exhibit phase-resolution of 11.25° with an RMS phase error of 5.2°. The insertion loss is 5.69±1.22 dB at 60-GHz and the return loss is better than 12 dB over 54-66 GHz. The chip demonstrates a compact size of only 0.034 mm2.